Could Marriage Be Disestablished? - Rivers, Julian (Tyndale bulletin, 2017)
In this paper, I respond to Dr Daniel Hill's argument that English law should cease to recognise marriage. Rather than focusing on general arguments of political theory for and against such a proposal I consider practical arguments based on the development of the law in response to injustice in family relations. A law of marriage of some sort seems inevitable. This conclusion is reinforced by the arguments of libertarian and feminist writers who seek to "abolish" marriage. Looked at more closely, they do nothing of the sort; they redefine it. Finally, I discuss the problem of unregistered marriages among British Muslims as an already existing example of marriage without the state. I conclude that law has to respond to existing social forms according to an idea of justice in domestic relations, and for that reason marriage cannot simply be "disestablished".